A charter for trainers in the prevention and management of workplace violence in mental health settings. Issue 2 (2014) - Brodie Paterson; Kevin McKenna; Vaughan Bowie
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to present the results of a Delphi study of trainers in the prevention and safer management of violence in mental health settings that sought to identify and clarify what represents best practice at a European level. Design/methodology/approach – A Delphi method was used to garner the views of a sample of 54 trainers involved in the training of managing violence and aggression on a draft charter of best practice. Findings – A high level of agreement was found with the suggested indicators of best practice but the levels of agreement varied in some key areas and respondents identified a series of omissions from the charter and a number of potential challenges to its implementation. Research limitations/implications – The sample was restricted to Europe and further research is planned to seek the views of a wider sample. Practical implications – The charter will provide a reference document for best practice in the interim. Social implications – Its implementation will require trainers to consciously identify the ethical implications not just of the content of their training buts its overall approach. Originality/value – The study is presently unique in its focus and context but further research in this area is underway designed to complement this study.